Activation of mass transfer processes at spark plasma sintering of zirconium dioxide; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Akarachkin S. A. (Numerical Simulation of Applied Problems, 2016)
Title screen